Differential foraging success across a light level spectrum explains the maintenance and spatial structure of colour morphs in a polymorphic bird. (2nd May 2016) - Tate, Gareth J.; Bishop, Jacqueline M.; Amar, Arjun
Abstract: Detectability of different colour morphs under varying light conditions has been proposed as an important driver in the maintenance of colour polymorphism via disruptive selection. To date, no studies have tested whether different morphs have selective advantages under differing light conditions. We tested this hypothesis in the black sparrowhawk, a polymorphic raptor exhibiting a discrete white and dark morph, and found that prey provisioning rates differ between the morphs depending on light condition. Dark morphs delivered more prey in lower light conditions, while white morphs provided more prey in brighter conditions. We found support for the role of breeding season light level in explaining the clinal pattern of variation in morph ratio across the species range throughout South Africa. Our results provide the first empirical evidence supporting the hypothesis that polymorphism in a species, and the spatial structuring of morphs across its distribution, may be driven by differential selective advantage via improved crypsis, under varying light conditions.